Laparoscopic-Assisted Vaginal Hysterectomy in a Patient with Placenta Percreta - Skinner, Bethany D. (Society of Laparoendoscopic Surgeons, 2012)
Placenta percreta is a problem encountered with increasing frequency due to the rising rate of cesarean delivery. Conservative management of this condition is associated with decreased perioperative morbidity. When hysterectomy is necessary, a laparoscopic approach can provide additional benefits. We present the case of a woman with placenta percreta with bladder invasion who was undergoing conservative management and then required delayed hysterectomy. Laparoscopic-assisted vaginal hysterectomy was successfully performed. We review the techniques used to ensure a good outcome and the advantages of a minimally invasive approach to hysterectomy in this patient with placenta percreta.